An Introduction to Regulatory Aspects Related to Medical Devices in Japan and Canada - Sharma, Yashika; Singh, Dilpreet; Singh, Amrinder (Current Indian Science, 2023)
BackgroundA medical device is a gadget that is used to identify, prevent, or treat illness or other medical conditions, but it does not work chemically on or within the body. It includes instruments, apparatus, implants, in vitro reagents, and similar or related items. The approval process for medical equipment in regulated markets (such as those in Canada and Japan) is one of the major concerns for their proper induction. The categorization of medical equipment and the procedure for their approval in these nations and their companions need to be clearly addressed in order to facilitate a better understanding of the regulations.AimThe regulatory considerations regarding the Japanese regulatory body for medical devices have been well discussed. Further, other aspects, such as the organization of the study of medical devices and the clearance process with the Ministry of Health, Labour, and Welfare's role in Japan's medical device industry, have been elaborated. Medical device licensing and application procedures in this regard with the leading Japanese medical equipment manufacturers have been revealed.Results/DiscussionIn Canada, medical equipment post-market surveillance on risk-based categorization has been revealed. The organisational structure of the medical equipment governing body and the Canadian approval process for medical instruments included by Health Canada with the top 10 medical technology setups in Canada have been elaborated in detail.ConclusionIn this review, regulatory aspects in Japan and Canada for understanding the direction and evolution of the medical device industry have been discussed. This analysis aims to provide a more comprehensive understanding of the regulatory framework governing the marketing authorisation of diagnostic and therapeutic medications in Japan and Canada to a global audience.
Keywords: Diagnostics